Uptake of oxidized lipids by the scavenger receptor CD36 promotes lipid peroxidation and dysfunction in CD8+ T cells in tumors - Xu, Shihao; Chaudhary, Omkar; Rodríguez-Morales, Patricia; Sun, Xiaoli; Chen, Dan; Zappasodi, Roberta; Xu, Ziyan; Pinto, Antonio F. M.; Williams, April; Schulze, Isabell; Farsakoglu, Yagmur; Varanasi, Siva Karthik; et al. (Immunity, 2021)
A common metabolic alteration in the tumor microenvironment (TME) is lipid accumulation, a feature associated with immune dysfunction. Here, we examined how CD8+ tumor infiltrating lymphocytes (TILs) respond to lipids within the TME. We found elevated concentrations of several classes of lipids in the TME and accumulation of these in CD8+ TILs. Lipid accumulation was associated with increased expression of CD36, a scavenger receptor for oxidized lipids, on CD8+ TILs, which also correlated with progressive T cell dysfunction. Cd36−/− T cells retained effector functions in the TME, as compared to WT counterparts. Mechanistically, CD36 promoted uptake of oxidized low-density lipoproteins (OxLDL) into T cells, and this induced lipid peroxidation and downstream activation of p38 kinase. Inhibition of p38 restored effector T cell functions in vitro, and resolution of lipid peroxidation by overexpression of glutathione peroxidase 4 restored functionalities in CD8+ TILs in vivo. Thus, an oxidized lipid-CD36 axis promotes intratumoral CD8+ T cell dysfunction and serves as a therapeutic avenue for immunotherapies.